2019
DOI: 10.1097/jnn.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Injury, Sleep, and Functional Outcome in Hospital Patients With Traumatic Brain Injury

Abstract: Problem: Uninterrupted nighttime sleep is associated with better cognition and functional outcomes in healthy adults, but the relationship between sleep and functional outcome in individuals hospitalized with severe TBI remains to be clarified. Objective: (1) Describe nighttime rest-activity variables-wake bouts (WB) (counts), total wake time (TWT) (minutes), and sleep efficiency (SE) (%; time asleep/time in bed)-in people on a neuroscience step-down unit (NSDU) post-TBI; (2) Describe association between injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Our findings are consistent with studies that show poor sleep in hospitalized patients with TBI (Chiu et al, 2013, 2014; Duclos et al, 2016; Williams et al, 2019; Wiseman-Hakes et al, 2016) and also with studies that cite loud sound and care-provision as significant disrupters of nighttime sleep for hospitalized patients in a neuroscience unit (Thomas et al, 2012; Uğraş et al, 2015). Light not being a significant finding is consistent with other studies that explored subjective nighttime light exposure perception and rest-activity cycles in hospitalized patients (Gathecha et al, 2016) and that reported low nighttime lux in a hospitalized sample (Bernhofer et al, 2014; Fanfulla et al, 2011) and in a sleep lab (Gooley et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with studies that show poor sleep in hospitalized patients with TBI (Chiu et al, 2013, 2014; Duclos et al, 2016; Williams et al, 2019; Wiseman-Hakes et al, 2016) and also with studies that cite loud sound and care-provision as significant disrupters of nighttime sleep for hospitalized patients in a neuroscience unit (Thomas et al, 2012; Uğraş et al, 2015). Light not being a significant finding is consistent with other studies that explored subjective nighttime light exposure perception and rest-activity cycles in hospitalized patients (Gathecha et al, 2016) and that reported low nighttime lux in a hospitalized sample (Bernhofer et al, 2014; Fanfulla et al, 2011) and in a sleep lab (Gooley et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…To measure the number of nighttime awakenings Actiwatch Spectrum Plus ® (Phillips Respironics, Bend, OR, USA) wrist actigraphy-watches (48 mm × 37 mm × 15 mm; wt., 31 g with band) were used; watches were calibrated to measure in 30-s epochs. Actigraphy is reliable and valid for assessing sleep disturbances (Ancoli-Israel et al, 2003; Morgenthaler et al, 2015) and has been used in hospitalized patients with TBI (Chiu et al, 2013, 2014; Duclos et al, 2016; Williams et al, 2019). Data were scored with Phillips Actiware ® software (Version 6.0.9) and a standard scoring algorithm developed by experienced sleep researchers at the University of Washington (Buchanan et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the burdensome nature of PSG and the lack of its availability in many hospital settings, alternatives such as ACG have been used to objectively quantitate sleep. 5,10,[20][21][22][23][24][25] Kamper and colleagues reported good agreement between ACG and PSG in a sample of veterans (n = 50) that was more chronic than the current sample. 10 Across other populations, agreement between ACG and PSG has varied from good agreement between sleep/ wake epoch classification to underestimation and/or overestimation of parameters as reported in this study.…”
Section: Discussionmentioning
confidence: 76%
“…Given the burdensome nature of PSG and the lack of its availability in many hospital settings, alternatives such as ACG have been used to objectively quantitate sleep 0025. Kamper and colleagues reported good agreement between ACG and PSG in a sample of veterans (n = 50) that was more chronic than the current sample 0010.…”
Section: Discussionmentioning
confidence: 99%